Features of a Low-Temperature Charge Density Wave in the Monoclinic Phase of NbS3 Manifested in the NMR and in Transport Properties - Semakin, A. S. (American Institute of Physics, 2025)
The relaxation of the transverse nuclear magnetization in the monoclinic phase of NbS3 has been studied by the 93Nb nuclear magnetic resonance method near the temperature TP2 = 150 K, at which a low-temperature charge density wave is formed. It has been shown that the critical slowing down of one of the vibrational modes of the lattice, which is quite slow even above TP2, occurs slightly below TP2. The transition at TP2 occurs not only in low-resistance samples, as thought previously, but also in high-resistance ones, and involves Nb atoms in the bulk of a sample. The transport properties of high-resistance samples, namely, the smearing of the depinning threshold for the charge density wave below TP2, confirm that the phase transition in them occurs at TP2. It has been concluded that the distortion of the lattice at TP2 is not due to the Peierls mechanism and can be attributed to the Keldysh–Kopaev transition. Another possible mechanism is the fluctuation distortion of the lattice above TP2 that prevents the sliding of the charge density wave.